Phosphatidylinositol‐3, 4, 5‐trisphosphate: Tool of choice for class I PI 3‐kinases. (13th June 2013) - Salamon, Rachel Schnur; Backer, Jonathan M.
<x xml:space="preserve">Abstract</x> Class I PI 3‐kinases signal by producing the signaling lipid phosphatidylinositol(3, 4, 5) trisphosphate, which in turn acts by recruiting downstream effectors that contain specific lipid‐binding domains. The class I PI 3‐kinases comprise four distinct catalytic subunits linked to one of seven different regulatory subunits. All the class I PI 3‐kinases produce the same signaling lipid, PIP3, and the different isoforms have overlapping expression patterns and are coupled to overlapping sets of upstream activators. Nonetheless, studies in cultured cells and in animals have demonstrated that the different isoforms are coupled to distinct ranges of downstream responses. This review focuses on the mechanisms by which the production of a common product, PIP3, can produce isoform‐specific signaling by PI 3‐kinases. Editor's suggested further reading in BioEssays: Phosphatidylinositol 4, 5‐bisphosphate: Targeted production and signaling Abstract How does SHIP1/2 balance PtdIns(3, 4)P2 and does it signal independently of its phosphatase activity? Abstract